Education with local wisdom paradigm: Teaching patterns of religious tolerance in Mbawa Village Donggo District, Bima Regency, West Nusa Tenggara - Iin Kurniati; Nafik Muthohirin (Universitas Negeri Yogyakarta, 2023)
This study aims to explore information related to the teaching pattern of religious tolerance, especially at the traditional Raju ceremony of the Mbawa Village community, Donggo District, Bima Regency. Mbawa residents are a diverse entity, both from religious and ethnic backgrounds. There are three different religions believed by the local community, namely Islam (78%), Catholicism (20%), and Protestantism (2%); and there are three ethnicities they profess namely Donggo, Flores, and Ambon. This article uses qualitative research methods with a descriptive analytical approach that aims to explain field data systematically and accurately, especially regarding the pattern of teaching religious tolerance values at the Raju traditional ceremony of the Mbawa community. This article uses Yusuf Al-Qaradawi's thesis in his thought which emphasizes the importance of teaching the values of religious tolerance for a pluralistic society. According to him, the teaching of the value of religious tolerance needs to be given to the community intensively, without discrimination towards certain religions or ethnicities. This study also wants to explain the traditions and cultural heritage of the Mbawa people through Emile Durkheim's thoughts on the role of socio-culture in bonding the relationship between religious communities. Durkheim said that to unite a plural community there needs to be a social role in the unity of rituals and common beliefs held by all citizens. This study concluded that the awareness of the Mbawa community to disseminate the values of tolerance in Raju traditional ceremonies through teaching patterns within families, educational institutions, and village and tribal government structures, succeeded in knitting positive relations between religious communities. Through the ceremony, residents also have a common awareness to coexist peacefully and nonviolently.